Assessment of Predictors of Left Atrial Volume Response to a Transcatheter InterAtrial Shunt Device (from the REDUCE LAP-HF Trial) - Hanff, Thomas C; Kaye, David M; Hayward, Christopher S; Post, Martijn C; Malek, Filip; Hasenfuβ, Gerd; Gustafsson, Finn; Burkhoff, Daniel; Shah, Sanjiv J; Litwin, Sheldon E; Kahwash, Rami; Hummel, Scott L; et al. (The American journal of cardiology, 2019)
In patients with heart failure and preserved or mildly reduced ejection fractions (EF ≥40%), implantation of an interatrial shunt device (IASD) resulted in heterogenous changes of the left atrial (LA) volume. Baseline characteristics that correlate with a favorable decrease in LA volume are unknown. We hypothesized that a larger ratio of left to right atrial volume at baseline would correlate strongly with LA volume decongestion following IASD implantation. Reduce Elevated LA Pressure in Patients With Heart Failure was a multicenter study of the safety and feasibility of IASD implantation. Sixty-four patients with EF ≥40% underwent device implantation along with baseline conventional echocardiograms, speckle tracking echocardiography, and resting and exercise hemodynamics. Higher LA compliance (-4.2%, p = 0.048) and right atrial reservoir strain (-0.8%, p = 0.005) were independently associated with a percent decrease in the systolic LA volume index from baseline to 6-months. In conclusion, greater LA volume reduction following IASD implantation is associated with higher baseline compliance of the left atrium and higher reservoir strain of the right atrium.
Keywords: Echocardiography, Doppler; výsledek terapie; Stroke Volume; Cardiac Surgical Procedures; Ventricular Function, Left; hodnocení rizik; Male; funkce levé komory srdeční; srdeční selhání; Risk Assessment; protézy a implantáty; Survival Rate; prognóza; Adult; Prospective Studies; dospělí; mužské pohlaví; lineární modely; tepový objem; Severity of Illness Index; srdeční síně; Hemodynamics; Prosthesis Implantation; Treatment Outcome; Multivariate Analysis; dopplerovská echokardiografie; lidé; ženské pohlaví; Cardiac Catheterization; srdeční katetrizace; Heart Failure; Humans; Linear Models; prediktivní hodnota testů; Prostheses and Implants; Prognosis; implantace protézy; stupeň závažnosti nemoci; hemodynamika; multivariační analýza; Female; kardiochirurgické výkony; lidé středního věku; Predictive Value of Tests; Heart Atria; míra přežití; Middle Aged; prospektivní studie